Feasibility of Introducing English as a Partial Medium of Instruction in Iranian Senior High Schools - Mohammad Reza Ghorbani (Universidad de La Sabana, 2020)
Viabilidad de introducir el inglés como medio parcial de instrucción en las escuelas secundarias iraníes  Viabilidade de introduzir o inglês como meio parcial de ensino nas escolas secundárias iranianas The use of Content and Language Integrated Learning has been increasing in many European countries simultaneous to the use of English as a medium of instruction in the non-Anglophone countries due to globalization and internationalization. Since the 1979 revolution, discussion on English as a medium of instruction in the Iranian formal education has been a taboo. This study aims to figure out the possibilities of introducing English as a partial medium of instruction (EPMI) for mathematics and science at senior high schools. The convergent mixed methods design was used to collect perspectives of students, content area teachers, parents, and administrative staff in Bojnord through e-mail interviews and survey questionnaires. The majority of the interviewees in the qualitative phase as well as most of the students, parents, teachers, and administrative staff in the quantitative phase have supported the possible use of EPMI. The findings of this study suggest future considerations to assist language education authorities in taking decisions to overcome students' language proficiency constraints while developing efficient and effective programs for CLIL. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Ghorbani, M. R. (2019). Feasibility of adopting English as a partial medium of instruction for mathematics and science subjects in Iranian senior high school. Latin American Journal of Content & Language Integrated Learning, 12(2), 292-320. https://doi.org/10.5294/laclil.2019.12.2.5 Received: 03/10/2019 Approved: 03/01/2020 Published: 11/05/2020